Representations of Memories through Art: The Artistic Work of Zdravko Dučmelić in Argentina - Molek, Nadia; Radovich, Juan Carlos; De Jager, Juan Esteban; Perez Molek, Amalia (Two Homelands, 2017)
This article discusses the topic of representations of memories through art using an interdisciplinary approach that connects contributions from the fields of anthropology and art history to the research problems of art and creative processes. Considering the artistic world of the Croatian painter Zdravko Dučmelić in Argentina as a case study, the main aim of the article is to explore how the sum of the acquired artistic/aesthetic habitus that mediated his artistic activities, memories and personal experiences was combined in the artist’s creative process. To this end we will present the formation of Dučmelić’s artistic and aesthetic habitus, and his insertion into the Argentinian sociocultural and artistic context, in order to explore Dučmelić’s creative process, paying special attention to the way that personal experiences, emotional stimuli and memories were resignified into artistic, symbolic and oneiric images.